SOME MORPHOLOGICAL OBSERVATIONS OF HIPPODAMIA VARIEGATE (GOEZE) (COCCINELLIDAE : COLEOPTERA) COLLECTED FROM SOUTH GUJARAT - JADHAV, DARSHANA S.; SHUKLA, ABHSHEK (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
An investigation was carried out during 2011-13 on the morphometrics of various ladybird beetle including, Hippodamia variegate (Goeze). The findings indicated that the mean body length of H. variegata was 3.76 mm and width 2.23 mm, the head length 0.89 mm and width 1.04 mm, whereas the antennal length, thorax length and width were 0.72, 2.01 and 2.05 mm, respectively. The fore leg length, middle and the hind leg length were 3.51, 2.58 and 4.05 mm, respectively. The elytra length and width were 3.27 mm and 1.43 mm, while the hind wing length and width were 4.41 mm and 1.67 mm, respectively. The abdomen length and width was 1.58 and 2.02 mm, respectively.